Metallurgical slag tailing mud-based cementing material and method for preparing artificial fish reef by using same
By developing metallurgical slag tail sludge-based gelling materials, the problems of low utilization rate of metallurgical slag tail sludge and high manufacturing costs of artificial reefs have been solved, and the effect of efficient utilization of solid waste resources and reducing marine repair costs has been achieved.
Patent Information
- Application Number
- CN202411882416.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-18
AI Technical Summary
The low utilization rate of metallurgical slag tail sludge leads to environmental pollution and waste of resources, and the high manufacturing cost of existing artificial reefs, limiting its application.
A metallurgical slag tail sludge-based gelling material was developed. By mixing steel slag tail sludge, desulfurized slag tail sludge, slag, 425# cement and desulfurized gypsum, gelling materials with good compressive strength and leaching safety performance were prepared, and artificial fish reefs were prepared using this material.
It realizes efficient utilization of metallurgical slag tail sludge, reduces the manufacturing cost of artificial reefs, and the compressive strength and leaching safety performance of the gelled materials meet the C20 standard, which is suitable for marine ecological restoration.
Smart Images

Figure CN119638223A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of solid waste resource utilization, in particular to a metallurgical slag tailing mud-based cementitious material and a method for preparing an artificial fish reef using the same. Background Art
[0002] Artificial reefs refer to structures set up artificially in waters to improve, repair and optimize the habitat of aquatic organisms, provide places for fish and other organisms to forage, reproduce, grow and develop, and achieve the purpose of protecting and increasing resources and increasing fish catches. While effectively controlling land-based pollution and deepening pollutant control, the restoration and improvement of offshore ecological environment are becoming increasingly important. Setting up artificial reefs and developing marine ranches are considered to be effective methods for offshore ecological restoration and promoting fishery production. The mechanism of marine ecological restoration of artificial reefs is to reduce the degree of eutrophication of water bodies through the adsorption of algae by artificial reefs, the filtering effect of organisms attached to reefs, the inhibitory effect of a large number of organisms in the reef area on red tide triggering factors, and the reef body's obstruction of the release of organic matter on the seabed. It has the effect of purifying water quality and reducing the occurrence of red tides.
[0003] Early artificial reefs were mostly made of natural stones, bricks, plants and other raw materials. Later, scrap cars, tires, ships, oil tanks, etc. were used in large quantities in the construction of artificial reefs. These natural materials and waste artificial reefs have disadvantages such as unreasonable reef cavity layout and small volume. In particular, scrap cars, tires, ships, oil tanks, etc. will also release a large amount of harmful substances in the seawater. In view of the above reasons, many coastal countries in the world have developed concrete artificial reefs.
[0004] Concrete artificial reefs can improve the marine ecological environment and are of great significance to marine ecological restoration. At the same time, the algae enriched on the surface of the reefs can also absorb CO2, which has a significant effect on improving the marine carbon sink under the background of "double carbon". There is a large demand for artificial reefs in my country, but the high manufacturing cost seriously limits its application.
[0005] As solid waste generated in the metallurgical process, the treatment and utilization of metallurgical slag tailings has always been an important issue in the field of environmental protection and resource recycling. At present, the utilization of metallurgical slag tailings in my country is characterized by low utilization rate and most tailings are treated as sludge. According to statistics, the amount of metallurgical slag tailings produced in my country each year is huge, but the comprehensive utilization rate is relatively low. This has led to a large amount of metallurgical slag tailings being simply piled up or landfilled. This treatment method not only occupies a large amount of land resources, but also easily causes environmental risks. Heavy metals and other harmful substances in tailings can easily penetrate into the ground in rainwater and pollute groundwater. In addition, some coastal metallurgical enterprises even discharge solid waste directly into rivers, seas and lakes, which not only seriously pollutes water resources, but also may cause environmental problems such as sludge blockage. Although my country has made certain progress in the resource utilization of metallurgical slag tailings in recent years, there are still challenges. On the one hand, due to the complex composition of metallurgical slag tailings, a single treatment method is often difficult to achieve ideal results. On the other hand, my country's current metallurgical solid waste treatment system is still imperfect, and technology research and development and application in many fields are still in the initial stage.
[0006] Therefore, improving the utilization rate of metallurgical slag and tailings and reducing environmental pollution have become urgent issues to be solved in my country's metallurgical industry. It is necessary to further strengthen technical research and development, explore more efficient and environmentally friendly methods for metallurgical slag and tailings treatment, and reduce the manufacturing cost of artificial reefs for marine restoration, which is of great research significance. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a metallurgical slag tailing mud-based cementitious material which can show good compressive strength for industrial application without adding admixtures such as activators and early strength agents, is simple to prepare, has good leaching safety performance, is environmentally friendly, and a method for preparing artificial fish reefs using the same.
[0008] The present invention is realized by the following technical scheme: a metallurgical slag tailing mud-based cementitious material is prepared by mixing the following components in parts by weight:
[0009] 0-4 parts of steel slag tailings;
[0010] Desulfurization slag tailings 0-6 parts;
[0011] 2-7 parts of slag;
[0012] 1-3 parts of 425# cement;
[0013] Desulfurization gypsum 0-2 parts.
[0014] Furthermore, the steel slag tailings are obtained by drying the flue gas generated during the treatment of converter slag and steel slag, and the specific surface area is 600-700m 2 / kg range, the content of free calcium oxide (f-CaO) is not higher than 0.5%, and the main chemical components are: CaO 40%-55%, SiO2 1.7%-15%, FeO11%-17%, MgO3.1%-11%.
[0015] Furthermore, the desulfurization slag tailings are obtained by drying the flue gas generated in the desulfurization slag treatment through a dust collector and recovered to a sedimentation tank, and the specific surface area is 600-750m 2 / kg range, the content of free calcium oxide (f-CaO) is not higher than 0.5%, and the main chemical components are: CaO 50%-60%, SiO2 1.7%-20%, FeO5%-17%, MgO 3.1%-10%.
[0016] Furthermore, the specific surface area of the slag is 450-550m 2 / kg range, and its main phases are grosvenorite and rhodonite.
[0017] Furthermore, the specific surface area of the desulfurized gypsum is 350-600m 2 / kg range, and its main component is calcium sulfate dihydrate (CaSO4·2H2O).
[0018] A method for preparing an artificial fish reef using the metallurgical slag tailing mud-based cementitious material as a raw material comprises the following steps:
[0019] S1. Weighing metallurgical slag tail mud-based cementitious materials and aggregates, and mixing them according to the mass ratio of metallurgical slag tail mud-based cementitious materials to aggregates of 1:(4-7), and mixing them evenly to obtain a mixture, wherein the aggregates are divided into coarse aggregates and fine aggregates, and the mass ratio of the coarse aggregates to the fine aggregates is (1-3):1, the coarse aggregates are natural crushed stone, and the fine aggregates are composed of natural sand and gravel and ground steel slag particles, and the mass ratio of the natural sand and gravel to the ground steel slag particles is (0-10):(10-0);
[0020] S2. Weigh the required water according to the water-to-binder ratio of (0.45-0.6):1;
[0021] S3. The mixture obtained in step S1 and the required water obtained in step S2 are mixed to form a uniform concrete mixture;
[0022] S4. The concrete mixture obtained in step S3 is made into a sample having a size of 100mm×100mm×100mm;
[0023] S5. The sample is placed in an environment with a temperature of 20° C. and a humidity of more than 95% for curing for 28 days to obtain an artificial fish reef.
[0024] Furthermore, the particle size distribution of the coarse aggregate is 20mm-19mm, 19mm-9.5mm, 9.5mm-4.75mm, and 4.75mm-2.36mm, wherein the weight ratio of coarse aggregate with a particle size of 20mm-19mm, a particle size of 19mm-9.5mm, a particle size of 9.5mm-4.75mm, and a particle size of 4.75mm-2.36mm is (0-10):(30-80):(20-60):(0-10).
[0025] Furthermore, the mass ratio of the natural sand and gravel to the ground steel slag particles is (4-8):(6-2).
[0026] Furthermore, the preparation method of the ground steel slag particles is as follows: the steel slag tailings with a particle size of 4.75mm-20mm are crushed twice by jaw crushing, and after magnetic separation, they are sieved through a 4.75mm sieve, and the material under the sieve is recorded as material A, the material A is disc-milled for 10s-30s and sieved through a 0.15mm sieve, and the material on the sieve is recorded as material B, and the material A and the material B are mixed in a weight ratio of 1: (1-3) to obtain the ground steel slag particles, and the particle size distribution thereof is 19mm-4.75mm, 4.75mm-2.36mm, 2.36mm-1.18mm, 1.18mm-0.6mm, 0.6mm-0.3 mm, 0.3mm-0.15mm, 0.15mm-sieve bottom, among which the weight ratios of ground steel slag particles with particle size of 19mm-4.75mm, particle size of 4.75mm-2.36mm, particle size of 2.36mm-1.18mm, particle size of 1.18mm-0.6mm, particle size of 0.6mm-0.3mm, particle size of 0.3mm-0.15mm, and particle size of 0.15mm-sieve bottom are (0-10):(10-15):(10-25):(20-31):(20-30):(5-15):(0-20).
[0027] The gelling material of the present invention has the following characteristics:
[0028] First, compared with the existing cementitious materials, the cementitious materials of the present invention have a simple composition and simple pretreatment, and do not require the addition of additives such as activators and early strength agents. It is composed of five components: steel slag tailings, desulfurization slag tailings, slag, 425# cement, and desulfurization gypsum. The tailings account for more than 40%, which maximizes the use of solid waste as raw materials and increases the utilization rate of solid waste resources. Secondly, while the composition is simplified, it can still show good cementitious properties due to the synergistic effect. From the perspective of chemical reactions, the synergistic effect between tailings, gypsum, and slag is based on their mutual excitation and reaction during the hydration process. Gypsum and desulfurization slag tailings act as activators to provide SO4 2-It can promote the hydration activity of steel slag tailings and slag and accelerate the hydration reaction. During the hydration process, the mineral components in the tailings and slag can dissociate and release ions. These ions react with the ions provided by gypsum in the solution to generate hydrates such as calcium aluminate (AFt) and hydrated calcium silicate (C-S-H) gel, thereby enhancing the strength of the cementitious material. In addition, from the perspective of physical filling effect, the synergistic effect between tailings, gypsum and slag is also reflected in their optimization of the void structure. Tailings can have a unique particle morphology and particle size distribution, which can fill the voids between slag and gypsum particles, making the cementitious material more compact. This physical filling effect helps to improve the overall performance and durability of the cementitious material. At the same time, as the hydration reaction proceeds, the generated hydration products will also fill the voids, further improving the microstructure of the cementitious material.
[0029] The steel slag tailings and desulfurization slag tailings have good safety, and the leaching concentration of heavy metal ions (Cr, Cu, Zn, Cd, Sb, Hg, Pb, etc.) is lower than the drinking water standard, and the safety is high. The artificial fish reefs prepared by this cementitious material and placed in seawater can quickly reduce the pH value of the surface of the artificial fish reefs to a pH value close to that of seawater, which is beneficial to the growth and habitat of aquatic organisms and promotes marine ecological restoration.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The gelling material of the present invention does not use any additives.
[0032] 2. The present invention recycles tailing mud, which is rare and has a large output and comprehensive utilization, thereby improving the solid waste resource utilization rate of the tailing mud.
[0033] 3. The synergistic effect of steel slag tailings, desulfurization slag tailings, slag, 425# cement and desulfurization gypsum shows high compressive strength and leaching safety, with high safety and heavy metal leaching lower than the drinking water standard.
[0034] 4. The processing method of each component of the cementitious material is simple, the preparation method is simple, and the cost of raw material processing is reduced. Compared with the existing use of steel slag as the raw material of the cementitious material, the present invention does not require crushing, screening, and magnetic separation through the processing line, which greatly reduces the energy consumption cost of raw material processing.
[0035] 5. The free calcium oxide content of metallurgical slag mud is low and does not require additional treatment. Compared with traditional cementitious materials and steel slag-based cementitious materials, the free calcium oxide content of steel slag when used in cementitious materials is <3%, while the free calcium oxide content of metallurgical slag mud is <0.5%. When metallurgical slag mud is used in the production of concrete and artificial fish reefs, it is not easy to react with water vapor in the air to cause cracking and has high stability.
[0036] 6. The artificial fish reef prepared by the cementitious material of the present invention is an effective means of marine environmental restoration. By simulating the natural reef structure, it provides a breeding, habitat and foraging place for marine organisms, promotes the recovery of the ecosystem and the improvement of fish diversity. The surface of the reef quickly becomes a hot spot for biological attachment, from microorganisms to small invertebrates, to fish, crustaceans and mollusks, gradually constructing a complex biological community and enhancing ecological stability. At the same time, it also improves the marine environment, such as improving water quality and dissolved oxygen content, promoting biological growth and reproduction, forming a virtuous cycle, and laying the foundation for the sustainable development of the marine ecosystem. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 and Figure 2 It is a schematic diagram of the attachment of organisms to the artificial fish reef of the present invention. DETAILED DESCRIPTION
[0038] The embodiments of the present invention will be described in detail below in conjunction with the examples, and the described examples are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] A metallurgical slag tailing mud-based cementitious material is prepared by mixing the following components by weight: 3 parts of steel slag tailing mud, 0 parts of desulfurized slag tailing mud, 4 parts of slag, 2 parts of 425# cement, and 1 part of desulfurized gypsum. The components are mixed uniformly by a mixer.
[0041] Among them, the chemical composition of steel slag tailings, desulfurization slag tailings, slag, 425# cement, and desulfurization gypsum are shown in Table 1. The detection method is: X-ray fluorescence spectrometry (XRF), using XRF-1800 X-ray fluorescence spectrometer to measure secondary X-rays for material composition analysis. Sand uses ISO standard sand and implements standard ISO679.
[0042] After the above-mentioned metallurgical slag tailing mud-based cementitious material is cast and formed, it is cured to different ages for compression test and leaching pH value test, wherein the compression test method is:
[0043] Weigh each component according to the above ratio. The steel slag tailings need to be ground to a specific surface area of 678.50m 2 / kg, the water-cement-sand ratio is 0.5:1:3, and the sample is prepared according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021). The sample size is 40mm×40mm×40mm, and it is cured at a temperature of 20°C and a humidity of more than 99.5%.
[0044] The compressive strength (Mpa) and curing pH value of mortar specimens at different ages are shown in Table 2.
[0045] A method for preparing an artificial fish reef using the metallurgical slag tailing mud-based cementitious material as a raw material comprises the following steps:
[0046] S1. Weigh metallurgical slag mud-based cementitious materials and aggregates, and mix them according to the mass ratio of metallurgical slag mud-based cementitious materials to aggregates of 1:3.67, and mix them evenly to obtain a mixture, wherein the aggregates are divided into coarse aggregates and fine aggregates, and the mass ratio of the coarse aggregates to the fine aggregates is 1.5:1. The coarse aggregates are natural crushed stones, and the fine aggregates are composed of natural sand and gravel and ground steel slag particles, and the mass ratio of the natural sand and gravel to the ground steel slag particles is 3:2.
[0047] S2. Weigh the required water according to the water-to-binder ratio of 0.55:1.
[0048] S3. Mix the mixture obtained in step S1 and the required water obtained in step S2 to form a uniform concrete mixture.
[0049] S4. The concrete mixture obtained in step S3 is made into a sample with a size of 100 mm×100 mm×100 mm.
[0050] S5. The sample is placed in an environment with a temperature of 20° C. and a humidity of more than 95% for curing for 28 days to obtain an artificial fish reef.
[0051] The test results of compressive strength (MPa) and pH value of curing solution of artificial fish reef concrete specimens at different ages are shown in Table 3.
[0052] Example 2
[0053] A metallurgical slag tailing mud-based cementitious material is prepared by mixing the following components by weight: 1 part of steel slag tailing mud, 1 part of desulfurized slag tailing mud, 6 parts of slag, 2 parts of 425# cement, and 0 part of desulfurized gypsum, and each component is mixed uniformly by a mixer.
[0054] Among them, the chemical composition of steel slag tailings, desulfurization slag tailings, slag, 425# cement, and desulfurization gypsum are shown in Table 1. The detection method is: X-ray fluorescence spectrometry (XRF), using XRF-1800 X-ray fluorescence spectrometer to measure secondary X-rays for material composition analysis. Sand uses ISO standard sand and implements standard ISO679.
[0055] After the above-mentioned metallurgical slag tailing mud-based cementitious material is cast and formed, it is cured to different ages for compression test and leaching pH value test, wherein the compression test method is:
[0056] Weigh each component according to the above ratio. The steel slag tailings need to be ground to a specific surface area of 678.50m2 / kg, the water-cement-sand ratio is 0.5:1:3, and the sample is prepared according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021). The sample size is 40mm×40mm×40mm, and it is cured at a temperature of 20°C and a humidity of more than 99.5%.
[0057] The compressive strength (Mpa) and curing pH value of mortar specimens at different ages are shown in Table 2.
[0058] A method for preparing an artificial fish reef using the metallurgical slag tailing mud-based cementitious material as a raw material comprises the following steps:
[0059] S1. Weigh metallurgical slag mud-based cementitious materials and aggregates, and mix them according to the mass ratio of metallurgical slag mud-based cementitious materials to aggregates of 1:3.67, and mix them evenly to obtain a mixture, wherein the aggregates are divided into coarse aggregates and fine aggregates, and the mass ratio of the coarse aggregates to the fine aggregates is 1.5:1. The coarse aggregates are natural crushed stones, and the fine aggregates are composed of natural sand and gravel and ground steel slag particles, and the mass ratio of the natural sand and gravel to the ground steel slag particles is 2:3.
[0060] S2. Weigh the required water according to the water-to-binder ratio of 0.55:1.
[0061] S3. Mix the mixture obtained in step S1 and the required water obtained in step S2 to form a uniform concrete mixture.
[0062] S4. The concrete mixture obtained in step S3 is made into a sample with a size of 100 mm×100 mm×100 mm.
[0063] S5. The sample is placed in an environment with a temperature of 20° C. and a humidity of more than 95% for curing for 28 days to obtain an artificial fish reef.
[0064] The test results of compressive strength (MPa) and pH value of curing solution of artificial fish reef concrete specimens at different ages are shown in Table 3.
[0065] Example 3
[0066] A metallurgical slag tailing mud-based cementitious material is prepared by mixing the following components in parts by weight: 0 parts of steel slag tailing mud, 4 parts of desulfurized slag tailing mud, 4 parts of slag, 2 parts of 425# cement, and 0 parts of desulfurized gypsum, wherein the components are mixed uniformly by a mixer.
[0067] Among them, the chemical composition of steel slag tailings, desulfurization slag tailings, slag, 425# cement, and desulfurization gypsum are shown in Table 1. The detection method is: X-ray fluorescence spectrometry (XRF), using XRF-1800 X-ray fluorescence spectrometer to measure secondary X-rays for material composition analysis. Sand uses ISO standard sand and implements standard ISO679.
[0068] After the above-mentioned metallurgical slag tailing mud-based cementitious material is cast and formed, it is cured to different ages for compression test and leaching pH value test, wherein the compression test method is:
[0069] Weigh each component according to the above ratio. The steel slag tailings need to be ground to a specific surface area of 678.50m 2 / kg, the water-cement-sand ratio is 0.5:1:3, and the sample is prepared according to the "Test Method for Strength of Cement Mortar (ISO Method)" (GBT 17671-2021). The sample size is 40mm×40mm×40mm, and it is cured at a temperature of 20°C and a humidity of more than 99.5%.
[0070] The compressive strength (Mpa) and curing pH value of mortar specimens at different ages are shown in Table 2.
[0071] A method for preparing an artificial fish reef using the metallurgical slag tailing mud-based cementitious material as a raw material comprises the following steps:
[0072] S1. Weigh metallurgical slag mud-based cementitious materials and aggregates, and mix them according to the mass ratio of metallurgical slag mud-based cementitious materials to aggregates of 1:3.67, and mix them evenly to obtain a mixture, wherein the aggregates are divided into coarse aggregates and fine aggregates, and the mass ratio of the coarse aggregates to the fine aggregates is 1.5:1. The coarse aggregates are natural crushed stones, and the fine aggregates are composed of natural sand and gravel and ground steel slag particles, and the mass ratio of the natural sand and gravel to the ground steel slag particles is 0:1.
[0073] S2. Weigh the required water according to the water-to-binder ratio of 0.55:1.
[0074] S3. Mix the mixture obtained in step S1 and the required water obtained in step S2 to form a uniform concrete mixture.
[0075] S4. The concrete mixture obtained in step S3 is made into a sample with a size of 100 mm×100 mm×100 mm.
[0076] S5. The sample is placed in an environment with a temperature of 20° C. and a humidity of more than 95% for curing for 28 days to obtain an artificial fish reef.
[0077] The test results of compressive strength (MPa) and pH value of curing solution of artificial fish reef concrete specimens at different ages are shown in Table 3.
[0078] Table 1 Analysis of components
[0079]
[0080]
[0081] Table 2 Compressive strength (MPa) and curing pH value of mortar test blocks at different ages
[0082] sample 7-day compressive strength 28 days compressive strength pH value of curing solution for 7 days pH value of curing solution after 28 days Example 1 18.3 30.54 11.85 12.01 Example 2 15.9 26.56 11.7 11.9 Example 3 13.23 22.06 11.9 12.05
[0083] Table 3 Compressive strength (MPa) and pH value of curing solution of artificial reef concrete specimens at different ages
[0084] sample 7-day compressive strength 28 days compressive strength pH value of curing solution for 7 days pH value of curing solution after 28 days Example 1 18.5 31.9 10.9 9.03 Example 2 16.7 27.85 10.8 9.6 Example 3 14.11 23.7 10.72 9.6
[0085] Table 4 Heavy metal ion leaching concentrations of artificial reef concrete specimens at different ages (ug / L)
[0086]
[0087]
[0088] The compressive strength of the cementitious material of the present invention is tested by using a water-cement ratio of 0.55:1. According to the "Test Method for Cement Mortar Strength (ISO Method)" (GBT 17671-2021), the cementitious material of the present invention is used to prepare mortar test blocks with a size of 40mm×40mm×40mm. The test blocks are cured in water at a temperature of 20°C for 7 days / 28 days. The compressive strength of mortar test blocks at different ages and the curing pH value are shown in Table 2, showing good compressive strength and leaching safety performance, reaching the C20 standard. The artificial fish reef test blocks made based on the cementitious material have a size of 100mm×100mm×100mm and are cured at a temperature of 20°C for 28 days. The compressive strength of artificial fish reef concrete test blocks at different ages and the pH value of the curing solution are shown in Table 3, and the heavy metal ion leaching concentration of artificial fish reef concrete test blocks at the same age is shown in Table 4, showing good compressive strength and leaching safety performance, and the strength reaches the C20 standard. When the artificial fish reef of the present invention is placed in a natural seawater environment, it provides a breeding, habitat and foraging place for marine organisms by simulating the natural reef structure, thereby promoting the recovery of the ecosystem and the improvement of fish diversity.
[0089] Compared with the existing cementitious materials, the cementitious materials of the present invention have simple composition and simple pretreatment, and do not need to add admixtures such as activators and early strength agents. Among them, tailings account for more than 40%, which maximizes the use of solid waste as raw materials and increases the utilization rate of solid waste resources. Therefore, it can solve the problem of reducing, harmless and resource-based industrial solid waste (tailings and slag), promote solid waste utilization and environmental protection, and has important research significance for large-scale consumption of industrial solid waste such as steel slag and tailings, while reducing the manufacturing cost of artificial reefs for marine restoration.
[0090] The cementitious material of the present invention and the artificial fish reef made based on the cementitious material are highly safe: the steel slag tailings and desulfurization slag tailings used have good safety, and the leaching concentration of heavy metal ions (Cr, Cu, Zn, Cd, Sb, Hg, Pb, etc.) is lower than the drinking water standard; the cementitious material does not produce free Ca(OH)2 after hydration, and can quickly reduce the pH value of the surface of the artificial fish reef placed in seawater to a pH value close to that of seawater, which is beneficial to the growth and habitat of aquatic organisms and promotes marine ecological restoration.
[0091] The above detailed description is a specific description of a feasible embodiment of the present invention. The embodiment is not intended to limit the patent scope of the present invention. Any equivalent implementation or modification that does not deviate from the present invention should be included in the patent scope of this case.
Claims
1. A metallurgical slag tailing mud-based cementitious material, characterized in that: By weight, it is made by mixing the following components: 0-4 parts of steel slag tailings; Desulfurization slag tailings 0-6 parts; 2-7 parts of slag; 1-3 parts of 425# cement; Desulfurization gypsum 0-2 parts.
2. The metallurgical slag tailing mud-based cementitious material according to claim 1, characterized in that: The steel slag tailings are obtained by drying the flue gas generated during the treatment of converter slag and steel slag, and the specific surface area is 600-700m 2 / kg range, the content of free calcium oxide (f-CaO) is not higher than 0.5%, and the main chemical components are: CaO 40%-55%, SiO2 1.7%-15%, FeO11%-17%, MgO 3.1%-11%.
3. The metallurgical slag tailing mud-based cementitious material according to claim 2, characterized in that: The desulfurization slag tailings are obtained by drying the flue gas generated in the desulfurization slag treatment through the dust collector and recovered to the sedimentation tank. The specific surface area is 600-750m 2 / kg range, the content of free calcium oxide (f-CaO) is not higher than 0.5%, and the main chemical components are: CaO 50%-60%, SiO2 1.7%-20%, FeO5%-17%, MgO 3.1%-10%.
4. The metallurgical slag tailing mud-based cementitious material according to claim 3, characterized in that: The specific surface area of the slag is 450-550m 2 / kg range, and its main phases are grosvenorite and rhodonite.
5. The metallurgical slag tailing mud-based cementitious material according to claim 4, characterized in that: The specific surface area of the desulfurized gypsum is 350-600m 2 / kg range, and its main component is calcium sulfate dihydrate (CaSO4·2H2O).
6. A method for preparing artificial fish reefs using the metallurgical slag tailing mud-based cementitious material according to any one of claims 1 to 5 as raw material, characterized in that: The following steps are involved: S1. Weighing metallurgical slag tail mud-based cementitious materials and aggregates, and mixing them according to the mass ratio of metallurgical slag tail mud-based cementitious materials to aggregates of 1:(4-7), and mixing them evenly to obtain a mixture, wherein the aggregates are divided into coarse aggregates and fine aggregates, and the mass ratio of the coarse aggregates to the fine aggregates is (1-3):1, the coarse aggregates are natural crushed stone, and the fine aggregates are composed of natural sand and gravel and ground steel slag particles, and the mass ratio of the natural sand and gravel to the ground steel slag particles is (0-10):(10-0); S2. Weigh the required water according to the water-to-binder ratio of (0.45-0.6):1; S3. The mixture obtained in step S1 and the required water obtained in step S2 are stirred evenly to form a uniform concrete mixture; S4. The concrete mixture obtained in step S3 is made into a sample having a size of 100mm×100mm×100mm; S5. The sample is placed in an environment with a temperature of 20° C. and a humidity of more than 95% for curing for 28 days to obtain an artificial fish reef.
7. The method for preparing artificial fish reefs using metallurgical slag tailing mud-based cementitious materials as raw materials according to claim 6, characterized in that: The particle size distribution of the coarse aggregate is 20mm-19mm, 19mm-9.5mm, 9.5mm-4.75mm, and 4.75mm-2.36mm, among which the weight ratio of the coarse aggregate with a particle size of 20mm-19mm, a particle size of 19mm-9.5mm, a particle size of 9.5mm-4.75mm, and a particle size of 4.75mm-2.36mm is (0-10):(30-80):(20-60):(0-10).
8. The method for preparing artificial fish reefs using metallurgical slag tailing mud-based cementitious materials as raw materials according to claim 7, characterized in that: The mass ratio of the natural sand and gravel to the ground steel slag particles is (4-8):(6-2).
9. The method for preparing artificial fish reefs using metallurgical slag tailing mud-based cementitious materials as raw materials according to claim 8, characterized in that: The preparation method of the ground steel slag particles is as follows: steel slag tailings with a particle size of 4.75 mm-20 mm are subjected to jaw crushing twice, and after magnetic separation, they are sieved through a 4.75 mm sieve, and the material under the sieve is recorded as material A; material A is disc-milled for 10s-30s and sieved through a 0.15 mm sieve, and the material on the sieve is recorded as material B; material A and material B are mixed in a weight ratio of 1:(1-3) to obtain ground steel slag particles, and the particle size distribution thereof is 19 mm-4.75 mm, 4.75 mm-2.36 mm, 2.36 mm-1.18 mm, 1.18 mm-0.6 mm, and 0.6 mm-0.3 mm , 0.3mm-0.15mm, 0.15mm-sieve bottom, among which the weight ratios of ground steel slag particles with particle size of 19mm-4.75mm, particle size of 4.75mm-2.36mm, particle size of 2.36mm-1.18mm, particle size of 1.18mm-0.6mm, particle size of 0.6mm-0.3mm, particle size of 0.3mm-0.15mm, and particle size of 0.15mm-sieve bottom are (0-10):(10-15):(10-25):(20-31):(20-30):(5-15):(0-20).
Citation Information
Patent Citations
Steel scoria tail mud composite slag micro mist agglutination material
CN101492261A
Preparation method for artificial fish reef concrete material with slag as main raw material
CN103159448A
Full steel slag roller compacted concrete and preparation method thereof
CN104058697A
Foam light material utilizing fly ash solid waste as well as preparation method and application of foam light material
CN113816678A